2012
DOI: 10.1590/s0102-695x2012005000115
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of guaco mouthwashes (Mikania glomerata and Mikania laevigata) on the disinfection of toothbrushes

Abstract: Guaco Mikania glomerata Spreng. and M. laevigata Sch. Bip. ex Baker, Asteraceae, has antimicrobial activity and may be helpful in reducing the incidence of oral diseases. This double-blinded randomized clinical trial aimed to evaluate the effi cacy of guaco mouthwashes on the disinfection of toothbrushes used by preschool children, tested positive for mutans streptococci (MS), as well as the quantifi cation of its coumarin contents by high performance liquid chromatography. Ethanol extracts were obtained by pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Batista et al (2014) reported the use of mouthwashes of chamomile and pomegranate extracts and suggested that both extracts have anti-inflammatory and antimicrobial properties. In a recent study conducted by our group (Lessa et al, 2012), a mouthwash known as guaco was prepared with ethanolic extracts of Mikania laevigata and Mikania glomerata. It showed antimicrobial activity against S. mutans and was evaluated as a toothbrush sanitiser; mouthwash prepared with M. glomerata had the same efficacy as the mouthwash with chlorhexidine 0.12% (gold standard).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Batista et al (2014) reported the use of mouthwashes of chamomile and pomegranate extracts and suggested that both extracts have anti-inflammatory and antimicrobial properties. In a recent study conducted by our group (Lessa et al, 2012), a mouthwash known as guaco was prepared with ethanolic extracts of Mikania laevigata and Mikania glomerata. It showed antimicrobial activity against S. mutans and was evaluated as a toothbrush sanitiser; mouthwash prepared with M. glomerata had the same efficacy as the mouthwash with chlorhexidine 0.12% (gold standard).…”
Section: Discussionmentioning
confidence: 99%
“…The standard strain used was ATCC 25175 ™ S. mutans. We performed a serial dilution of the toothbrush rinse with a concentration range of 100 to 0.01 µg/ml to calculate the minimum inhibitory concentration (MIC) (Lessa et al, 2012). In total, 100 μl bacitracin sucrose broth (SB20), a selective enrichment broth (Davey and Rogers, 1984), 100 μl of the inoculum and 50 μl of the test solution were added to each well.…”
Section: Preparation Of Essential Oil Toothbrush Rinse P Heptaphyllummentioning
confidence: 99%
See 3 more Smart Citations